Realization of Principles of Pedagogical Morality in Teacher’s Professional Activity - Nataliya Kazakova; Leonida Pisots’ka (Pedagogical Discourse, 2012)
The article reveals the main principles of pedagogical morality in teacher’s activity: pedagogical humanism, pedagogical optimism, collectivism, civicism and petriotism. The content of the article elucidates the main ways of realization of these principles in teacher’s professional activity.